A cut-off value of shear wave speed to distinguish nonalcoholic steatohepatitis candidates. Issue 2 (January 2019) - Suda, Takeshi; Kanefuji, Tsutomu; Abe, Atsushi; Nagayama, Itsuo; Hoshi, Takahiro; Morita, Shinichi; Yagi, Kazuyoshi; Hatakeyama, Shigeaki; Hayatsu, Masafumi; Hasegawa, Noboru; Terai, Shuji
Abstract : Abstract: To distinguish and characterize nonalcoholic steatohepatitis (NASH) candidates from among medical checkup visitor diagnosed with nonalcoholic fatty liver diseases (mcNAFLDs). A cut-off value has not been established to differentiate NASH at the earliest stage in NAFLD. Shear wave speed (SWS) was measured in the livers of 480 mcNAFLDs. NASH candidates were screened out by adopting a statistically defined cut-off value of SWS and were characterized in terms of food preference. SWS ranged between 1.11 and 2.18 m/s and fit a Gaussian distribution (r 2  = 0.98) with an average and SD of 1.324 and 0.0847 m/s, respectively, in 320/160 males/females 64.4 (interquartile range 57.3–69.4) years old. The average plus SD (1.41 m/s) screened out 82 (17.1%) NASH candidates, who were significantly older (66.8 vs. 64.1 years old, P  = 0.001) and had higher fibrosis 4 index values (1.58 vs. 1.33, P  < 0.0001) than the remaining mcNAFLDs. The number of patients with a BMI greater than 25 kg/m 2 was 118 (29.6%) mcNAFLDs and 34 (41.5%) NASH candidates, with a significantly higher frequency in NASH candidates ( P  = 0.05). Obese patients preferentially ate fatty acids in general, while NASH candidates preferred to consume several long-chain unsaturated fatty acids irrespective of their BMI. These results suggest that NASH candidates who have a longer disease duration and pathological progression can be distinguished from mcNAFLDs by a statistically defined cut-off value of SWS. The defined value indicates that there are different food habitats associated with obesity and NAFLD progression. Abstract : Supplemental Digital Content is available in the text